Socio-Political Conditions for Christians in Egypt - Gabbay, Shaul M. (European Scientific Journal, ESJ, 2018)
For those who have studied the history of religious tensions in Egypt, the current rising tide of violence against Christians in the country should come as no surprise. Persecution of Christians in Egypt dates back for centuries. In recent years—particularly during the past decade—we have witnessed a greater interest in understanding the violence, not only in academia, but among the interested general population as well. This has led to an upsurge in academic writings and in media articles discussing the issue. After a thorough literature review, I have discovered that many of the pieces focus on the empirical, while often neglecting the normative. While empiricism is important for any research endeavor, this paper seeks to focus more on the narratives on the ground. As a sociologist for three decades, I have worked closely with the Egyptian Christian immigrant community in the U.S. and have regularly been called to testify in asylum courts across the U.S. regarding the issues of religious intolerance in Egypt. Over the years, I have conducted countless interviews with these individuals. As such, I have used their personal stories as a starting point for my academic inquiries. As a case study, I have selected three personal narratives to include in this analysis. All of the individuals’ names have been changed in order to safeguard their identity. For this paper, I have specifically chosen individuals from different backgrounds, genders, education levels, social standings, and geographical location. In doing so, I was able to piece together a larger narrative that demonstrates how the persecution of Christians in Egypt is not limited to one group or another—it is widespread throughout Egyptian society. In the end, I was able to discover that each of the individuals suffered in different ways. However, they all suffered given one basic commonality—being Christian in Egypt.